Pertumbuhan Lembaga Reksadana Syariah Di Indonesia - Mukhamad Zakariya (Universitas Islam Lamongan, 2017)
The development of capital markets in Indonesia is encouraging. It brings a positive impact on the development of the investment system in accordance with the basic principles of sharia, in the capital markets sector in Indonesia, or better known by the term Islamic capital market. Islamic capital market is developed with the aim of accommodating the needs of Muslims in Indonesia that performs investment in capital market products in accordance with the basic principles of sharia. As we know that Indonesia is a country with a predominantly Islamic population makes Indonesia has a potential market for Islamic products. The problems of this study are the factors that influence the growth and development of Sharia Mutual Funds in Indonesia until 2014. The purpose of this study is to determine the factors that affect the growth and development of Sharia Mutual Fund in Indonesia, in particular on the list of Sharia Mutual Funds issued by OJK (Financial Services Authority) to 2014. This research is a qualitative research that does not test the hypothesis, but is intended to gain a deeper understanding of the various variables describing the past circumstances or phenomenon is happening today. The data used in this research is secondary data. This research is conducted by analyzing data collected by the author, which is derived from the issuer's financial statements, related websites, journals of sharia economic, sharia economic papers and other related sources. The analysis technique used by the author in this study is descriptive-qualitative method, a method that is done by collecting data, compiling and interpreting the results in order to obtain a clear picture of the growth and development of Sharia Mutual Funds in Indonesia until 2014. The results of this study shows that the main factor affecting the growth and development of Sharia Mutual Fund in Indonesia is the active role of government, both in terms of regulation or other supports, affecting various aspects, such as the development of product innovation. Keywords: Mutual Funds, Islamic Mutual Fund, the Government of Indonesia